A Linguistic Skills, Sociolinguistic Abilities, and Communicative Proficiency of Senior High School Students - Alo, Merien (International Journal of Arts, Sciences and Education, 2023)
This mixed-method research was conducted to determine the level of linguistic skill, sociolinguistic ability, and communicative proficiency of Senior High School students. To measure students' linguistic skills, data were collected using a 25-item assessment of vocabulary skills and a 25-item assessment of grammar skills that the researcher personally created; questionnaire on sociolinguistic ability, which consists of 10 items on discursive ability and 10 items on strategic ability personally created by the researcher; and one (1) set of question for assessing oral communication to measure communicative proficiency. Another instrument that will be used in this study is the Focus Group Discussion (FGD) guide. The FGD served the purpose to validate the results of the survey and to give multiple and meaningful interpretations to the data gathered. The researcher used statistical tools to analyze the descriptive data such as frequency count, percentage, mean, standard deviation, one way analysis of variance (ANOVA) and Pearson r and alpha level set at .05. The findings of this study show that the level of linguistic skills based on vocabulary skills and grammar skills of senior high school students is "high". The level of sociolinguistic ability based on discursive ability and strategic ability is "high". Also, the level of communicative proficiency based on students' oral communication is "moderate". It was also found that there was "no significant difference" in communicative efficiency between the students' level of linguistic skills. Meanwhile, "there is a significant difference" in communicative efficiency with the level of sociolinguistic ability. It was also found that "there is a significant relationship" between linguistic skills and sociolinguistic ability; “no significant relationship” between linguistic skills and communicative efficiency; and "there is a significant relationship" between sociolinguistic ability and communicative efficiency of senior high school students.